2014
DOI: 10.1108/raf-04-2012-0035
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of involuntary delisting rate in the Egyptian IPO equity market

Abstract: Purpose – The purpose of this paper is to examine the determinants of involuntary delisting rate for the Egyptian initial public offerings (IPOs) issued over the period 1992-2009. Design/methodology/approach – A definition of survival time that considers the date when the new Egyptian listing rules were enforced to track delisting status for each IPO firm for five survival years is relied on. Binary logit regression analysis is used to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
(89 reference statements)
1
5
0
Order By: Relevance
“…Jiang and Wang, in China; Algebaly et al. , in Egypt) and their results are mainly in line with the findings for developed markets.…”
supporting
confidence: 86%
“…Jiang and Wang, in China; Algebaly et al. , in Egypt) and their results are mainly in line with the findings for developed markets.…”
supporting
confidence: 86%
“…Initial public offering (IPO) survival refers to the extent of time a public corporation remains listed on the stock market [1,2]. The IPO survival comes to an end as it delists from the respective stock market, irrespective of whether delisting occurs voluntarily (e.g., conversion to a private firm, merger and acquisition) [3,4] or involuntary (e.g., forced delisting by court or exchange, financial distress leading to liquidation, hostile merger and acquisition) grounds [5]. Over the last three decades, this question has raised concerns about the sustainable survival of newly listed IPOs in capital markets across the globe [6].…”
Section: Introductionmentioning
confidence: 99%
“…Based on resource based hypothesis, firms with higher IPO proceeds are expected to survive longer as they are expected to have the required resources for innovation and advertising activities. Jain and Jayaraman (1999), Willenborg and McKeown (2001), Bhabra and Pettway (2003), Boubakri, Kooli, and L'Her (2005), Kooli and Meknassi (2007), and Algebaly et al (2014) found a significant negative relationship between offering size and delisting rate.…”
Section: Delisting In Athens Stock Exchange 353mentioning
confidence: 86%